Rapaki wahine whakamaumahara: memories of the Rapaki Branch Māori Women's Welfare League - Plumridge, Elizabeth (Canterbury University Press, 2008)
"Documenting the early days of the Rapaki Maori Women's Welfare League, this recollection strives to authenticate the oral histories of the early members that created the opportunity for Maori and Pakeha women to meet and trade skills. As membership of the branch changes, fewer and fewer people can speak with authority on the league's evolution, but this history chronicles the available facts and anecdotes that demonstrate the development of this important union."–BOOK JACKET.
Keywords: history; mana wāhine; māori womens welfare league; social conditions; wāhine māori

Terror in our midst?: searching for terror in Aotearoa New Zealand - Keenan, Danny (Huia Publishers, 2008)
" On 15 of October 2007, three hundred police officers dressed in full riot gear, including balaclavas and sunglasses, raided the township of Ruatoki which lies at the northern end of the Ureweras. At the same time as Ruatoki was being lockeddown, police raids were taking place in other parts of the country. By the end of the day, 17 people were reported as arrested; four from Wellington, six in Auckland, one in Palmerston North, one in Hamilton and five in the Bay of Plenty area. The 'global war on terror', launched in the US five years earlier, had finally arrived in New Zealand "–Publisher website., Contributors: Pou Temara, Moana Jackson, Sue Abel, Maria Bargh, Te Urikore Biddle, Luke Crawford, Rawinia Higgins, Richard Hill, Brendan Hokowhitu, Craig Innes, Tonga Karena, Danny Keenan, Ocean Rīpeka Mercier, Dominic O'Sullivan, Māmari Stephens and Alice Te Punga Somerville.
Keywords: civil Rights; police; prevention; terrorism